PENERAPAN PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON-EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS III SDN 003 PAGARAN TAPAH DARUSSALAM - Rosnia Rosnia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This study is a class action based on the results of observations in SDN 003 Pagaran Tapah Darussalam, met some of the symptoms or phenomena in the learning process, among others: of the 18 students, only 10 people, which totaled completeness criteria minimal set school namely 65, while the other students have not reached the kkm, teaching and learning process education citizenship (civics) does not stimulate students to engage actively follow the lessons, it is apparent from the activities of children busy with activities respectively, learning only emphasizes the terms of cognitive less engaging students, so that students are less self-contained, so the lack of student learning outcomes, especially on the subjects of civics. Based on the above, it can be concluded that the low student learning outcomes. To improve student learning outcomes, this research used non-example of cooperative learning example in citizenship education lessons class III SDN 003 Pagaran Tapah Darussalam. The formulation of the problem in this research are: does the implementation of cooperative learning mode non-examples examples can improve learning outcomes civics lesson in third grade students of SDN 003 Pagaran Tapah Darussalam. This research was carried out in three cycles and each cycle is done in one meeting. In order to study this class action work well without barriers obstructing the smooth running of the study, researchers compiled stages are passed in classroom action research, namely: 1) planning/ preparatory actions, 2) implementation of the action, 3) observation and reflection. After the implementation of cooperative learning tife examples non-examples, it is known the first cycle student learning outcomes at an average value of 67.2. Then, after reflection and improvement against the weaknesses of learning. Unknown at the second cycle of the average value of student learning outcomes achieved on the average value of 75.6, and the third cycle, student learning outcomes also meninkat with the average achieved in the classical style was 80.8 in both categories. This means that all students have reached kkm is set so that it indicates the success of the study. Due to the success indicator set has exceeded 75%.